2019
DOI: 10.1080/20473869.2019.1690859
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perspectives on how to improve the support for persons with an intellectual disability and challenging behaviors: a concept mapping study

Abstract: Introduction: People with an intellectual disability (ID) are at risk of developing challenging behavior. Although previous research provided important insights into how to support people with an ID and challenging behavior, it remains unclear what various stakeholders consider to be the most essential aspects to further improve their support. Method: Statements regarding aspects perceived necessary to improve the support to people with an ID and challenging behavior were collected in focus groups. Afterwards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
(63 reference statements)
3
9
0
Order By: Relevance
“…This underlines the relevance of involving different participant groups in research. Overall, our results confirm outcomes of research that it is important to invest in building relationships between service users and support staff (e.g., Nijs et al, 2021 ; Olivier‐Pijpers et al, 2020a ). This includes respect, trust, and getting to know each other well.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This underlines the relevance of involving different participant groups in research. Overall, our results confirm outcomes of research that it is important to invest in building relationships between service users and support staff (e.g., Nijs et al, 2021 ; Olivier‐Pijpers et al, 2020a ). This includes respect, trust, and getting to know each other well.…”
Section: Discussionsupporting
confidence: 88%
“…For example, they reported that support staff need to be experienced (life as well as work experience), confident, have a low level of expressed emotions (e.g., show no fear), and stay calm in case of tension. These characteristics are in line with research about support to service users with intellectual disability who display challenging behaviour (Nijs et al, 2021 ; Willems et al, 2016 ). Nearly all the statements of service users applied to activities and interpersonal relations with a direct impact on the service user, described by Bronfenbrenner as the microsystem (Bronfenbrenner, 1994 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations